(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article discusses the content of the organization of the educational process based on collaborative learning, the establishment of cooperative relations between teachers, administration and students and teachers’ organizations, leaders, parents, the public. Went Factors for the development of student learning motivation using collaborative technology and the achievement of high results through the implementation of the principles of humanization of the educational process are identified.